2021
DOI: 10.1039/d1tb00428j
|View full text |Cite
|
Sign up to set email alerts
|

Selenium atom on phosphate enhances specificity and sensitivity of DNA polymerization and detection

Abstract: DNA polymerization is of high specificity in vivo. However, its specificity is much lower in vitro, which limits the advanced applications of DNA polymerization in ultrasensitive nucleic acid detection. Herein...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These results indicated that the improvement by the dNTPαSe substrates was not caused by increasing the substrate concentrations, which was consistent with our previous studies. 29,32…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicated that the improvement by the dNTPαSe substrates was not caused by increasing the substrate concentrations, which was consistent with our previous studies. 29,32…”
Section: Resultsmentioning
confidence: 99%
“…Though these reagents are often used as commercial optimizers and kit enhancers for polymerase chain reactions, their effect via the buffer improvement is limited. Nevertheless, the supplementary dNTPαSe significantly enhanced the polymerase reaction accuracy, 29,32 thereby greatly improving the specificity and sensitivity of PCR detection. Clearly, our simple and convenient Se-atom strategy has great potential in nucleic acid amplification and detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the mechanism of the de novo DNA synthesis, we have explored the polymerization with the modified dNTPs (Figure ). We have discovered that the de novo synthesis with polymerases (Pol I, Bst, and Taq functioning under 37, 63, and 72 °C, respectively) can be inhibited by the modified dNTPs (such as dNTPαSe; Figure B). Furthermore, we have found that although the polymerase generates byproduct DNAs more and faster in the presence of the nickase than its absence, dNTPαSe can inhibit the byproduct polymerization as well (Figure D).…”
Section: Resultsmentioning
confidence: 99%